Promoting Social Entrepreneurship among Entrepreneur with Disabilities in Contribution for Community - Rozali Norhasyikin; Abdullah Shuhairimi; Jamaluddin Jamsari; Ramil Abdul Jalil; Hussin Noor Salwani; Ahmad Aida Zainab (MATEC Web of Conferences, 2018)
Looking forward of the uniqueness social entrepreneurship (SE) new phenomena born from entrepreneurships felid. Because of that it is a new step point for the entrepreneur with disabilities (EWD) to be part of social entrepreneurship environments. Where SE, link the positive impact for society creating by entrepreneur that understand that social problem give a big opportunities for profit or nonprofit activity that can be solve creatively. This give a lot of advantage of EWD to contributes to community in the term of “social impact”. This conceptual paper maps SE and EWD in contribution to community with the important role play by stakeholder in promoting SE. This conceptualization enhances understanding of EWD in SE and clear picture of role play by stakeholder give chances for EWD contributes to community.